Bilingualism and auditory processing abilities: performance of adults in dichotic listening tests - Gresele,Amanda Dal Piva (2013)
Purpose: To evaluate and compare the dichotic listening abilities in non-hearing-impaired adults monolingual speakers of the Brazilian Portuguese language (CG) and simultaneous Brazilian Portuguese-German (GG) bilingual speakers or successive Brazilian Portuguese-Italian bilingual speakers (IG). Methods: This is about an observational, descriptive, transverse and quantitative research. The sample consisted of 87 subjects aged between 18 and 55 years, divided into: Control Group (CG), of 30 monolingual speakers of Brazilian Portuguese; Study Group A (SGA), of 31 simultaneous Brazilian Portuguese-German bilingual speakers; and Study Group I (SGI), of 26 successive Brazilian Portuguese-Italian speakers. The individuals were submitted to the Dichotic digits test (DDT) and to Staggered Spondaic Words (SSW). Results: The DTT results showed difference in right ear and total scores when comparing SGA to CG. Comparing the CG and the SGI, it was observed difference in right and left ears and total scores. Comparing the SGA and the SGI, no difference was observed between the groups. Results of SSW showed that both bilingual groups were significantly better in the right and left ears scores and even in total one when compared to CG. Comparing the SGA and the SGI, the SGI showed better significant scores in the right ear and total. Conclusion: Bilingual experiences seem to influence positively the ability of high predictability dichotic listening, evaluated by DDT, and the low predictability dichotic listening, evaluated by SSW test. The SSW results also showed statistically significantly better results for successive Brazilian Portuguese-Italian bilingual speakers when compared to simultaneous Brazilian Portuguese-German speakers.